Pemberdayaan Ibu Menyusui dan Keluarga untuk Mencegah Stunting: Implementasi Media Edukasi SMART ASIK di Tanjungpinang - Marella, Marella; Ridayani, Rita; Harianja, Ristina Rosauli; Batubara, Kartika Sri Dewi (Borneo Community Health Service Journal, 2025)
This study focuses on the high prevalence of stunting in Tanjungpinang City, reaching 15.7% based on the 2022 SSGI data. The low rate of exclusive breastfeeding, at only 58%, significantly contributes to this issue. The objective of this community service project is to enhance the knowledge and skills of breastfeeding mothers through educational media in the form of flashcards called SMART ASIK. The research method includes providing education and training to breastfeeding mothers and posyandu cadres about the importance of exclusive breastfeeding and the technique of oxytocin massage. Results indicate an increase in mothers' knowledge to 90%, with exclusive breastfeeding practices rising to 75%. Cadres' skills also improved by 85%. The discussion highlights the necessity of ongoing support from posyandu cadres and community involvement in the educational process. The conclusion of this study is that the SMART ASIK program is effective in improving the knowledge and skills of breastfeeding mothers, which in turn can reduce the prevalence of stunting in the area. Future plans include regular monitoring and evaluation to ensure the sustainability of the program